Determination of the Disability Premium there is Life Insurance with Annual Payment for Type Benefit Waiver of Premium - marsela, esti; Yosmar, Siska; Damayanti, Septri (Universitas Negeri Padang, 2023)
When there is a work accident that results in someone becoming disabled or sick, it often leads to termination of employment (layoff) for reasons of productivity. A person who has a chance of having a work accident needs to buy a disability life insurance policy to reduce the financial losses that occur. One type of disability benefit in life insurance is the waiver of premiums. The purpose of this study is to determine the amount of annual disability premium that will be paid to be able to benefit from the type of benefit waiver of premium on dual-purpose life insurance either manually or using Excel Visual Basic for Application. The results showed that the calculation of annual premiums can be generalized that the older the insured, the greater the premium paid. Meanwhile, the greater the policy term, the smaller the premium paid.